Financial Health Analysis of Bank Tabungan Negara Using RGEC Method: 2021–2024 Period - Anna Valensia Christianty de Fretes (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the financial health of PT Bank Tabungan Negara (Persero) Tbk for the period 2021–2024 using the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) method. This approach complies with regulations issued by the Financial Services Authority (OJK) to comprehensively assess the performance of commercial banks. A descriptive quantitative approach was employed, utilizing secondary data from the company’s official website and the Indonesia Stock Exchange in the form of annual financial reports. The results indicate that regarding the Risk Profile, the Non-Performing Loan (NPL) ratio remained in a healthy category, while the Loan to Deposit Ratio (LDR) was less healthy in the early years but improved in subsequent periods. The Good Corporate Governance (GCG) aspect consistently achieved a score of 2 (healthy) over the four-year period. Meanwhile, the Earnings aspect, measured by the Return on Assets (ROA) ratio, fell into a fairly healthy category. The Capital aspect, assessed through the Capital Adequacy Ratio (CAR), consistently demonstrated a very healthy condition. Overall, the RGEC analysis indicates that Bank BTN is in a healthy condition, although liquidity and profitability challenges still require strategic attention in the future.